Bukhara and the Muslims of Russia Sufism, education, and the paradox of islamic prestige - Frank, Allen J., 1964- (Leiden ; Boston : Brill, 2012)
In Bukhara and the Muslims of Russia Allen Frank examines the relationship between Muslims in Russia and the city of Bukhara, examining paradoxes emerging the city's Sufism-based Islamic prestige, and the emergence of Islamic reformism in Russia.
Includes bibliographical references and index.
Print version record.
Keywords: Islam -- Russia (Federation); Muslims -- Russia (Federation); Sufism -- Russia (Federation); SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Islam; Muslims; Sufism; Russia (Federation); Electronic books; Electronic books